Analisis Tipe HOTS dan LOTS dalam Asesmen Madrasah Matematika Tingkat Lanjut di MAN 1 Trenggalek - Sudarmanto, Sudarmanto; Mubarok, Moch Yazid; Munir, Ulfa Saikhul; Sutopo, Sutopo; Musrikah, Musrikah (Papanda, 2026)
The demands of 21st century learning emphasize the importance of developing higher-order thinking skills through assessments aligned with the revised Bloom’s Taxonomy. However, mathematics assessment practices at the secondary education level are still predominantly focused on measuring lower-order thinking skills. This study aims to describe the characteristics and proportion of Higher Order Thinking Skills (HOTS) and Lower Order Thinking Skills (LOTS) items in the Advanced Mathematics Madrasah Assessment at Senior High School 1 Trenggalek. The study employed a descriptive approach using a combination of qualitative and quantitative methods through document analysis of 40 assessment items consisting of multiple-choice, complex multiple-choice, and short-answer questions. Each item was analyzed based on the cognitive levels of the revised Bloom’s Taxonomy (C1–C6) and classified into HOTS and LOTS categories. The results indicate that the assessment is still dominated by LOTS items, particularly at the C3 (applying) level, which emphasizes procedural skills. HOTS items were identified at the C4 and C5 levels, while the C6 (creating) level has not yet been accommodated. In terms of item format, multiple-choice questions tend to measure LOTS, whereas complex multiple-choice and short-answer questions are more likely to assess HOTS. These findings suggest that the assessment remains in a transitional phase toward strengthening higher order reasoning.